Comprehensive In Silico Analysis of the NHX (Na+/H+ Antiporter) Gene in Rice (Oryza sativa L.) - Hoa Hai Thi Bui; Duong Huy Nguyen; Le Thu Thi Dinh; Hang Thu Thi Trinh; Thoa Kim Vu; Van Ngoc Bui (International Journal of Plant Biology)
The Na+/H+ antiporter (NHX) gene family plays a pivotal role in plant salt tolerance in regulating intracellular Na+ and H+ homeostasis. In this study, seven candidate OsNHX genes (OsNHX1 to OsNHX7) were identified in the rice genome and classified into three phylogenetic clusters (Vac, Endo, and PM) based on their predicted subcellular localization. Five OsNHX gene pairs (OsNHX1/OsNHX2, OsNHX1/OsNHX3, OsNHX1/OsNHX4, OsNHX2/OsNHX6, and OsNHX5/OsNHX6) were found to have arisen from dispersed duplication events and exhibited purifying selection, indicating functional conservation. Analysis of cis-regulatory elements (CREs) revealed a diverse range of elements associated with tissue-specific expression, hormone signaling, and stress responses, particularly to dehydration and salinity. Notably, CREs associated with tissue/organelle-specific expression and stress responses were the most abundant, suggesting a potential role for OsNHX genes in regulating growth, development, and stress tolerance in rice. Importantly, expression profiling revealed that OsNHX1, OsNHX2, OsNHX3, and OsNHX5 were upregulated under salt stress, with significantly higher expression levels in the salt-tolerant rice cultivar Pokkali compared to the salt-sensitive cultivar IR64. Our findings provide a comprehensive analysis of the evolutionary, structural, and functional features of the OsNHX gene family and highlights their critical role in rice salt tolerance, offering insights into potential applications for crop improvement.